Barriers for local authorities to invest in disaster risk reduction: evidence from Zimbabwe. Issue 1 (2nd January 2022) - Mavhura, Emmanuel; Mapuva, Jephias
ABSTRACT: Local authorities (LA) are vested with authority to preside over the affairs of local communities. This authority comes with responsibilities of reducing disaster risks and losses. Disaster risk reduction (DRR) has been a key goal of global frameworks for minimizing risk and losses from disasters. Despite global efforts to reduce disaster risk, research into what hinders LA in investing for DRR is limited. Using case study material from two rural councils in Zimbabwe, this study examined barriers that constrain LA in investing in DRR for resilience. The study used interviews that involved local authority and civil protection officials, the academia, policy makers and disaster practitioners. Results show that LA in Zimbabwe are constrained by inadequate legislative authority, unclear mandates for DRR and a lack of necessary resources. The study concludes that LA need strengthening through legislative reforms, devolution, and injection of financial and material resources to invest in DRR strategies.